ANALISIS SISTEM AKUNTANSI PELUNASAN PIUTANG PADA PERUSAHAAN DISTRIBUTOR FARMASI - Nur Amirotul Suroyah; Erry Andhaniwati (JURNAL LENTERA AKUNTANSI, 2024)
Cash is the most liquid asset because it is easily accessible, but it is also vulnerable to misuse. This study to find out and prove that the cash receipt system for the receivables settlement at a pharmaceutical distributor company is in accordance with the provisions of the applicable accounting system. This includes the separation of related functions, the required documents are in accordance with the provisions, and whether the accounting records used as a management control tool are already in place and running effectively. This study uses a qualitative analysis research method. Sugiyono (2020) stated that qualitative analysis is a research technique that interprets field data or natural conditions. In this study, the researcher used primary data from field observations and interviews with employees in the cash and recording department. The results of the study show that the function incompatibility related to cash receipts for the receivables settlement in the company is with Mulyadi's theory (2024). This is because the company does not have an internal control function. Companies should increase internal control to reduce the risk of fraud. A strong monitoring system will ensure that cash receipts for receivables repayment are in accordance with the company's policies and applicable regulations.